Novel interaction study of Th(IV) and Zr(IV) with 4-sulfonatocalix[6]arene: experimental and theoretical investigation - Rathod, N.V. (Polyhedron, 2017)
Calixarenes based ligands are well known in the extraction of heavy metal ions. The modifications at lower as well as upper rim increase the new possibilities of metal extraction in terms of quantum and selectivity of metal. In comparison to calix[4]arene, complexing nature of calix[6]arene is less studied due to its large size and flexible nature. In the present study, 4-sulfonatocalix[6]arene (SCX6) is synthesized and an attempt has been made to understand its complexation behavior with Th(IV) and Zr(IV) metal ions. The effect of different solvents has been examined along with calculation of binding constants for better complexation possibilities. Though in general, its complexation proves to be at 1:1 stoichiometry with respect to ligand and metal, the specific metals show its characteristic modes of interaction with the ligand. This has been understood through IR spectroscopic analysis and density functional theory based first principle studies. 1H NMR spectra of SCX6 and its complexes with Th(IV) and Zr(IV) metal ions was established. IR, UV–Vis, fluorescence spectroscopic studies provided a systematic understanding about the binding behavior of these two metals including interference possibilities from other metals.
Keywords: 4-Sulfonatocalix[6]arene; DFT; metal complexation; Th(IV) Zr(IV)